PEMANFAATAN BARANG BEKAS SEBAGAI MEDIA PEMBELAJARAN KOSA KATA BAHASA INGGRIS - Siska Rizkiani; Gartika Pandu Bhuana; Rissa San Rizqiya (LP4MK STKIP PGRI Lubuklinggau, 2019)
The learning component is needed to support an effective and efficient learning process. One of those components is the media. Some studies find the lack of use of media in teaching English to early childhood, especially the teaching of vocabulary. Therefore, this service aims to equip teachers' skills and creativity in making English learning media by using items in the surrounding environment, especially used materials such as cardboard, bottled water, paper, straws, etc.. The method used in this service is training. Training was given to English teachers in Jalancagak Village, Subang on August 10, 2019. As a result, the teacher was basically capable and quite creative in utilizing used materials as learning media. However, this must continue to be motivated and developed so as to create innovative and attractive learning. Some of the instructional media produced are snakes and ladders, letter boards, and car puppets. Learning media from used materials, however, has advantages that are not inferior to technology-based learning media. In addition to the low cost, the rules of utilizing used goods are easy and familiar to students. In addition, teachers can also develop students' creativity by inviting them together to make media from used materials.